Mesoporous Cu–Cu2O@TiO2 heterojunction photocatalysts derived from metal–organic frameworks - Zhao, Wenling; Liu, Chengcheng (RSC advances, 2020)
This study reveals a unique Cu–Cu2O@TiO2 heterojunction photocatalyst obtained with metal–organic framework as the precursor, which can be utilized in dye photodegradation under visible light irradiation. The composition, structure, morphology, porosity, optical properties and photocatalytic performance of the obtained catalysts were all investigated in detail. The Cu–Cu2O@TiO2 nanocomposite is composed of lamellar Cu–Cu2O microspheres embedded by numerous TiO2 nanoparticles. Methylene blue, methyl orange and 4-nitrophenol were used as model pollutants to evaluate the photocatalytic activity of the Cu–Cu2O@TiO2 nanocomposite for dye degradation under visible light irradiation. Nearly 95% decolourisation efficiency of Methylene blue was achieved by the Cu–Cu2O@TiO2 photocatalyst within 3 h, which is much higher than that of TiO2 or Cu2O catalysts. The excellent photocatalytic activity was primarily attributed to the unique MOF-based mesoporous structure, the enlarged photo-adsorption range and the efficient separation of the charge carriers in the Cu–Cu2O@TiO2 heterojunction.